Lamar archaeology : Mississippian chiefdoms in the deep South - Williams, J. Mark; Shapiro, Gary (University of Alabama Press, 1990)
A Dan Josselyn Memorial Publication Lamar Archaeology provides a comprehensive and detailed review of our knowledge of the late prehistoric Indian societies in the Southern Appalachian area and its peripheries. These Lamar societies were chiefdom-level groups who built most of the mounds in this large region and were ancestors of later tribes, including the Creeks and Cherokees. This book begins with a history of the last 50 years of archaeological and historical research and brings together for the first time all the available data on this early culture.
"A Dan Josselyn memorial publication."
Keywords: Lamar culture.; Indians of North America -- Southern States -- Antiquities.; Chiefdoms -- Southern States.; Southern States -- Antiquities.; Peuples autochtones -- États-Unis (Sud) -- Antiquités.; Chefferie (Anthropologie) -- États-Unis (Sud); États-Unis (Sud) -- Antiquités.; HISTORY -- State & Local -- General.; Antiquities; Chiefdoms; Indians of North America -- Antiquities; Lamar culture; Southern States